Pengaruh Pengetahuan Wajib Pajak, Kesadaran Wajib Pajak, Dan Sanksi Pajak Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor Di Semarang - Kurnia Mawaddah; Andi Kartika; Muhammad Ali Ma'sum (Journal of Economic, Bussines and Accounting (COSTING), 2023)
Motor vehicle tax consists of annual tax and tax once every five years. Taxpayer compliance is the fulfillment of their tax obligations through tax regulations. This study was conducted to obtain information and analyze several causes of changes in taxpayer compliance in Semarang, such as taxpayer knowledge and consciousness, as well as tax sanctions. Research sampling technique with accidental sampling technique. The use of this type of data in the study is primary data. The population in the study includes taxpayers who own and control motor vehicles included in the list at SAMSAT Semarang 1 in 2022. The results of taxpayer knowledge testing showed that it did not have a significant reaction on taxpayer compliance. For the moment, taxpayer consciousness testing and tax sanctions show a significant influence on taxpayer compliance. Keywords: knowledge, consciousness, sanctions, compliance